2012
DOI: 10.1590/s0102-695x2011005000172
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcer effect of epoxy-carvone

Abstract: Epoxy-carvone is a monoterpene present in essential oils of various plants. It is a derivative of carvone, which has an epoxy group instead of the α-and β-unsaturated ketone group present in carvone. As recent studies have shown that several alcohol terpenes and compounds containing α, β-unsaturated ketone groups present antiulcer effect, the main of the present study was to evaluate the antiulcer effect of epoxy-carvone. The models of ulcers induced by ethanol and indomethacin were used in this study. Epoxy-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
(25 reference statements)
2
11
0
Order By: Relevance
“…It is important to emphasize that is the first time that the gastroprotective activity of (1), caryophyllene oxide (3), kaurenoic acid (4), quercitrin (5) and afzelin (6) as pure compounds is showed. These results corroborate with the literature, which shows that terpenes and flavonoids exhibit protective effects on gastric ulcer and its activities are associated with cytoprotective mechanisms (Hiruma- Lima et al, 2006;Siqueira et al, 2012;Klein-Júnior et al, 2012;Santin et al, 2014). In addition, in the acute toxicity study, no signs of toxicity were observed after C. langsdorffii extract administration at the dose of 2000 mg/kg, at any time during the observation.…”
Section: Resultssupporting
confidence: 92%
“…It is important to emphasize that is the first time that the gastroprotective activity of (1), caryophyllene oxide (3), kaurenoic acid (4), quercitrin (5) and afzelin (6) as pure compounds is showed. These results corroborate with the literature, which shows that terpenes and flavonoids exhibit protective effects on gastric ulcer and its activities are associated with cytoprotective mechanisms (Hiruma- Lima et al, 2006;Siqueira et al, 2012;Klein-Júnior et al, 2012;Santin et al, 2014). In addition, in the acute toxicity study, no signs of toxicity were observed after C. langsdorffii extract administration at the dose of 2000 mg/kg, at any time during the observation.…”
Section: Resultssupporting
confidence: 92%
“…This indicates that the vasorelaxation caused by eugenol and linalool is NO-dependent whereas the vasorelaxing actions of carvone are NO-independent. The results obtained in this study are supported by reports that both eugenol and linalool induce in vivo antispasmodic effects which are endothelium released nitric oxide dependent whereas carvone acts by NO-independent mechanisms in rat isolated stomach preparations (11, 31, 32). …”
Section: Discussionsupporting
confidence: 89%
“…Tannins have also been reported to contribute immensely in gastroprotection (Dragana et al, 2009;Vasconcelos et al, 2010) while some saponins also protect the gut from ulcerogenic agents (Yoshikawa et al, 2008;Nwidu and Nwafor, 2009). A study conducted in Siqueira et al (2012), had reported the role of terpinoids in the prevention of ulcer and the healing of existing ulcers. The role of flavonoids in gastroprotection cannot be over ruled (Mota et al, 2009;Hussaini et al, 2012).…”
Section: Discussionmentioning
confidence: 99%